Simultaneous inhibition of cholinesterase and antagonism of histamine H3 receptors alleviates cognitive deficits and mitigates apoptosis in scopolamine-induced amnesia in mice - Ebdah, Wajd; Thomas, Shilu Deepa; Eissa, Nermin; Jayaprakash, Petrilla; Łażewska, Dorota; Kieć-Kononowicz, Katarzyna; Sadek, Bassem (Frontiers in Behavioral Neuroscience, 2026)
IntroductionAlzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline and memory deficits. Mounting evidence highlights the role of cholinergic and histaminergic neurotransmissions in the pathophysiology of AD. Hence, developing agents that target multiple neurotransmitter systems may provide improved therapeutic benefits.MethodsThis study investigated the effects of acute systemic administration of E100, a dual-active cholinesterase inhibitor (ChEI) and histamine H3 receptor (H3R) antagonist, on scopolamine (SCO)-induced memory impairment in male C57BL/6 mice. Behavioral assessments, including the Novel Object Recognition Test (NORT), Y-Maze test (YMT), Three-Chamber Test (TCT), Fear Conditioning test (FCT), and Elevated Plus Maze (EPM), were conducted to assess cognitive performance while biochemical analyses assessed apoptotic markers, oxidative stress, neuroinflammation and acetylcholinesterase activity.ResultsSystemic administration of E100 (10 mg/kg, i.p.) significantly improved memory function in SCO-induced amnesia, as evidenced by enhanced short-term memory (STM) (p < 0.001) and long-term memory (LTM) (p < 0.01) performance in the NORT, as well as improved spatial memory in YMT (p < 0.001) and FCT (p < 0.001; for cued fear memory) and (p < 0.001; for contextual fear memory). Additionally, E100 treatment in the TCT, improved social memory (p < 0.001) and alleviated SCO-induced anxiety-related deficits in the EPM (p < 0.001). Moreover, treatment with E100 (10 mg/kg, i.p.) attenuated SCO-induced neuroinflammation by reducing TNF-α and IL-1β levels and mitigated oxidative stress by increasing GSH and SOD while decreasing MDA levels in the hippocampus and cerebellum (p’s < 0.001). E100 also reduced caspase-1 activity (p < 0.001), suggesting its anti-apoptotic effect. Furthermore, E100 attenuated the elevated AChE activity observed in SCO-induced amnesic mice (p < 0.01), providing effects comparable to those of the reference drug Donepezil.DiscussionThese findings provide extensive in vivo evidence of the neuroprotective effects of E100, demonstrating its ability to ameliorate memory deficits, mitigate neuroinflammation and restore oxidative as well as AChE activity balance. By targeting both cholinergic and histaminergic dysfunction in the brain, E100 offers a promising therapeutic strategy for AD and related neurodegenerative disorders. This study highlights the potential role of dual-active ChEIs and H3R antagonists in memory impairment, and addressing multiple neuropathological mechanisms underlying AD.